KECEMASAN DAN SELF EFFICACY TERHADAP KEMAMPUAN MAHASISWA MENGIKUTI PEMBELAJARAN DARING - Wardati Humaira (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
The COVID-19 phenomenon has an impact on the implementation of education, one of which is online learning policies. This new regulation resulted in students having to adapt to the new system which had several challenges in its implementation. This study aims to determine the effect of anxiety and self-efficacy on students' ability to participate in online learning. This research is a quantitative research using explanatory research survey method, using a cross sectional approach. The statistical test used for the analysis was chi square at the 95% confidence level (? = 5%). The results showed that there was an influence of anxiety and self-efficacy on the ability of students to participate in online learning with each p value = 0.001.